NKT cells - new players in CAR cell immunotherapy? - Kriegsmann, Katharina; Kriegsmann, Mark; Bergwelt‐Baildon, Michael von; Cremer, Martin; Witzens-Harig, Mathias (European journal of haematology, 2018)
Low levels of peripheral blood natural killer T (NKT) cells in cancer patients and a favorable outcome associated with a high number of tumor-infiltrating NKT cells demonstrated in several studies indicated the important role of these immune cells in the antitumor response. With effective antitumor immunity via direct tumor lysis, cytokine modulation of effector cells and regulation of immunosuppressive cells, type I NKT cells display interesting features/properties for the rapidly developing chimeric antigen receptor (CAR) technology. Due to their restriction to the monomorphic HLA-like molecule CD1d, but not to the polymorphic human leukocyte antigen (HLA), NKT CAR cells show potential for enabling autologous and allogeneic/off-the-shelf cancer immunotherapy. Promising results were obtained in preclinical NKT CAR cell studies, but clinical trials have not yet been conducted. In this review, we summarize the biological features of NKT cells, their role in antitumor immunity and recent advances in the development of NKT CAR cells.
Gesehen am 29.10.2019